Relationship between Toddler Birth Weight History, Breastfeeding, and Infections Diseases in Toddlers wasting Age 12-59 Months - Nabila, Noor 'Aisya; Widyastuti Hariati, Niken; Pratiwi, Niken (Jurnal Riset Pangan dan Gizi, 2025)
Wasting is a problem of acute malnutrition that affects growth, development, and increases the risk of morbidity and mortality in toddlers. The prevalence of wasting in the working area of ​​the East Martapura Health Center is 21.4%, higher than the national average. This study aims to determine the relationship between birth weight history, breastfeeding, and infectious diseases in wasting toddlers aged 12-59 months in the working area of ​​the East Martapura Health Center. This type of research is observational analytic with a case control approach. A sample of 96 toddlers consisting of 48 wasting toddlers (cases) and 48 non-wasting toddlers (controls) were taken using cluster random sampling. Data were collected through interviews, anthropometric measurements, and KMS/KIA documentation. Data analysis used the Chi-Square test. The results of the univariate analysis showed that toddlers with a history of LBW were 27%, did not receive exclusive breastfeeding 69.7%, and had a history of infectious diseases 75%. The results of the bivariate analysis showed a significant relationship between birth weight history and wasting (p=0.000; OR=6.689), breastfeeding with wasting (p=0.001; OR=4.956), and infectious diseases with wasting (p=0.018; OR=3.212). Toddlers with a history of LBW, not receiving exclusive breastfeeding, and having a history of infectious diseases have a higher risk of wasting. It is recommended that health centers improve education about exclusive breastfeeding and preventing infectious diseases in toddlers